An experience on linguistic revitalization of Aymara in Lima-Peru - Suxo Yapuchura, Moisés (2017)
This article shows a brief systematization of an Aymara linguistic revitalization experience. It was implemented through two workshops during 2015 and 2016 in the framework of the Program for the Recovery, Development and Dissemination of Aymara Language and Culture which is promoted by the Aimara3 Collective in Lima. These workshops are part of a set of strategies to recover, revive and develop the Aymara language and culture in Peru. This program is aimed at children whose mother tongue is Spanish, but their parents are originally / or have Aymara ancestry, who in their vast extension are citizens of the Unicachi district, in Yunguyo province, Puno region.